Bio-based silica-reinforced caprolactam-toughened epoxy nanocomposites. (March 2016) - Kanimozhi, K; Prabunathan, P; Selvaraj, V; Alagar, M
In this work, industrially valuable and versatile nylon 6 precursor material caprolactam has been used as a toughener for diglycidyl ether of bisphenol A epoxy resin (caprolactam epoxy (CPE)) along with glycidyl-functionalized bio silica (GRS) derived from rice husk, which was used as a reinforcement to obtain hybrid nanocomposites with improved properties. Caprolactam (20 wt%) and epoxy (80 wt%) have been reinforced with varying weight percentages (0.5, 1.0 and 1.5 wt%) of GRS cured with diaminodiphenylmethane and characterized using different analytical techniques. Data obtained from mechanical studies indicate that the value of tensile strength, flexural strength and impact strength of 1.5 wt% GRS-reinforced caprolactam-toughened epoxy blend composites were enhanced to 135, 77 and 162%, respectively, compared with those of neat epoxy matrix. Similarly, the values of glass transition temperature and char yield were enhanced to 21 and 22%, respectively, whilst retaining inherent surface and insulating behaviour. Data from morphological studies infer the homogenous and uniform distribution of GRS in the CPE hybrid nanocomposites. From the data obtained from different studies, it is suggested that the hybrid composite materials developed in this work have potential use as coatings, adhesives, sealants, matrices and composites for different industrial and engineering applications in the place of conventional epoxy composites for improved performance and enhanced longevity.